Pelaksanaan Manajemen Kewirausahaan Sosial Melalui Peternakan Generasi Lestari Farm Dalam Perspektif AlQur’an - Hardi, Luthfi; Mahmud, Hamidullah (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Implementation (Actuating) as one of the functions and stages of management, is often interpreted as an effort to move or carry out. In an institution, organization or company, actuating can be interpreted as moving or giving direction to theresourcesin theinstitution,whether human resources or otherresources. Mobilizinghuman resources is a process that goes through starting from human resource planning, recruitment, education and training of human resources, as well as themotivation provided by those resources. while mobilizing otherresourcesis an effortto maximize the use of existing resources or mobilize organizational elements tocarry out all planned activities. In the context of implementing this management,the author discusses social entrepreneurship carried out by Generasi Lestari Farmwhich focuses on animal husbandry, namely sheep and goats. Socialentrepreneurship is a community-based alternative that hasthe potential to perfect the development process. combining innovative ideas for social change, carried out by applying business strategies and skills. And of course seeing how the social entrepreneurship journey process contains Islamic values as in the verses of theKoran which provide direction to Muslims to carry out a business or buying and selling (livestock) that is halal and good.